Fluorescent N-doped carbon dots for both cellular imaging and highly-sensitive catechol detection. (September 2015) - Li, Hao; Kong, Weiqian; Liu, Juan; Liu, Naiyun; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract: N-doped carbon dots (NCDs) obtained by one-step reflux treatment of C3 N4 with ethane diamine possess good water dispersibility, strong visible fluorescence, low toxicity, proton adsorption capacity, and photo-induced electron-accepting/donating abilities. Based on these unique properties, we demonstrate that the obtained NCDs can be used as a good fluorescent probe for cellar imaging without any further functionalization. Further, the NCDs are combined with laccase (LAC) to form NCDs–laccase (NCD–LAC) hybrids, which are sensitive, stable, and of low cost for the precise detection of catechol and catechol derivatives.